Investigating in utero fetal death: outcome of internal medicine consultation. (27th July 2017) - Belhomme, Nicolas; Le Noir De Carlan, Marine; Lescoat, Alain; Le Gallou, Thomas; Rouget, Florence; Loget, Philippe; Jego, Patrick
Abstract: Aim: The objectives were to determine the frequency of in utero fetal death (IUFD) related to placental disorders and to assess the frequency of antiphospholipid antibodies syndrome (APS) among women referred to the internal medicine department. Methodology: A retrospective clinical study conducted in Rennes University Hospital, France. From January 2007 to December 2014, 53 women who presented an IUFD at 14 weeks or more of gestational age were included. The main cause for each IUFD was determined by expert agreement. Primary outcome was to analyze the final etiologies diagnosed and the prevalence of IUFD related to placental disorders. Secondary outcomes included the frequency of APS among patients with IUFD of placental origin and the pathological and clinical features associated with APS. Results: IUFD resulted from placental disorders in 36/53 (68%) patients, and remained unexplained in 11 cases (20.8%). Among the 36 patients with placental disorders, APS was diagnosed in five (13.9%) cases, and four (11.1%) patients were considered as having 'non‐criteria' APS. History of thrombosis ( P = 0.001) and placental infarcts ( P = 0.047) were significantly associated with APS. Conclusion: Placental disorders were the major cause for IUFD in patients who were referred to internal medicine specialists. Importantly, APS was seldom found in patients with placental disorders. Venous thromboembolism history and placental infarcts were both significantly associated with APS. Further studies are needed in order to deepen our understanding of the physiopathology of placental disorders and its underlying causes among non‐APS women, and to determine the best treatment regimen for future pregnancies.